Comparison of best track parameters of RSMC, New Delhi with satellite estimates over north Indian Ocean - GOYAL, SUMAN; MOHAPATRA, M.; SHARMA, A.K. (MAUSAM, 2013)
Hkkjr ekSle foKku foHkkx ¼vkbZ- ,e- Mh-½ ,d izknsf’kd fof’k"V izdkj ds ekSle dsUnz gksus ds dkj.k pØokrh; fo{kksHkksa ¼lh-Mh-,l½ dk ekWuhVju ,oa iwokZuqeku nsus ds fy, ftEesokj gS blds varZxr pØokrh; fo{kksHksa ls lacaf/kr lHkh izdkj ds vk¡dM+s ftlesa vonkc ,oa m".kdfVca/kh; pØokr ¼Vh- lh-½ 'kkfey gS] dk laxzg] lalk/ku ,oa HkaMkj.k fd;k tkrk gS vkSj mRrjh fgUn egklkxj ¼,u- vkbZ- vks-½ esa cuus okys pØokrksa ds ekxZ dks lgh&lgh fu/kkZfjr djus esa budk mi;ksx fd;k tkrk gSA _rq ds i'pkr~ pØokrh; fokksHkksa ds fo’ys"k.k ds kjk fdlh pØokrh; fo{kksHk dh fLFkfr ,oa mldh rhozrk dk fu/kkZj.k pØokr dh vof/k ds nkSjku dh vU; fo’ks"krkvksa ds lkFk&lkFk fd;k tkrk gS ftls ge csLV VSªfdax ds uke ls tkurs gSaA csLV VSªfdax izfØ;k mRrjh fgUn egklkxj lfgr fo’o esa vyx&vyx izdkj dh gS vkSj ;g ekWuhVju ,oa fo’ys"k.k ds lk/ku rFkk izfØ;k esa fHkUurk ds dkj.k gksrh gSA ;|fi pØokrh; fo{kksHkksa ds LFkku ,oa rhozrk dk ekWuhVju djus ds fy, Hkw&LFkSfrd mixzg gh eq[; midj.k ekuk tk jgk gSA mRrjh fgUn egklkxj esa pØokrh; fo{kksHkksa ds csLV VSªd ds LFkku ,oa rhozrk ds fu/kkZj.k ds fy, mixzg dh Hkwfedk vkSj mldh lhek dk vkdyu djus ds fy, dqN iz;kl fd, x, gSA vr% izknsf’kd fof’k"V izdkj ds ekSle dsUnz ¼vkj- ,l- ,e- lh-½ ubZ fnYyh ds csLV VSªd izkpyksa ds vk/kkj ij pØokrh; fo{kksHkksa ds LFkku ,oa rhozrk dh rqyuk bulSV vkSj dYiuk mixzgksa ds vk/kkj ij vkbZ- ,e- Mh- ds mixzg izHkkx }kjk vkdfyr ifj.kkeksa ls djus ds fy, ,d v/;;u fd;k x;k gSA mRrjh fgUn egklkxj] caxky dh [kkM+h rFkk vjc lkxj esa vk, pØokrh; fo{kksHkksa ds LFkkuksa ds fu/kkZj.k esa vkSlr varj Øe’k% 39 fd- eh-] 40 fd- eh- ,oa 37 fd- eh- ik, x, gSA dqy ?kVukvksa esa ls yxHkx 65 izfr’kr ds LFku fu/kkZj.k esa 50 fd- eh- ;k de dk varj ik;k x;k vkSj mRrjh fgUn egklkxj esa laiw.kZ ?kVukvksa esa ls 6 izfr’kr esa 100 fd- eh- dk vFkok blls vf/kd dk varj ik;k x;kA caxky dh [kkM+h esa ;g varj 62 izfr’kr rFkk 6 izfr’kr dk Fkk vksj vjc lkxj esa yxHkx 70 izfr’kr ,oa 5 izfr’kr dk ik;k x;kA LFkku fu/kkZj.k esa varj Vh uacj esa o`f) ds lkFk /khjs&/khjs de gksrk tkrk gSA tc caxky dh [kkM+h] vjc lkxj vkSj mRrjh fgUn egklkxj esa flLVe dh rhozrk Vh-&4-0 ;k vf/kd ¼vfrizpaM pØokrh; rwQku vkSj mPp rhozrk½ gks rks ;g varj yxHkx 30 fd-eh- dk gksrk gSA pØokrh; fo{kksaHkksa ds LFkku esa varj ds LFkkfud forj.k dks ns[krs gq, ;g dgk tk ldrk gS fd ;g varj leqnz rV ds fudV vf/kd jgrk gS vksj tSls& tSls ge rV ls nwj tkrs gS ;g de gksrk tkrk gSA yxHkx 85-5 izfr’kr ?kVukvksa esa csLV VSªd dh rhozrk mixzg ds }kjk vkdyu ls esy [kkrh gSA tcfd mixzg vk/kkfjr rhozrk 9-5 izfr’kr ?kVukvksa esa de vkdfyr gqbZ gS ¼mixzg izHkkx }kjk vkdfyr Vh- uacj csLV VSªd Vh- uacj ls de gS½] mRrjh fgUn egklkx esa yxHkx 5 izfr’kr ?kVukvksa esa ;g vf/kd ¼mixzg izHkkx }kjk vkdfyr Vh- uacj csLV VSªd Vh- uacj ls vf/kd½ vkdfyr gqbZ gSSA LFkkfud forj.k dh n`f"V ls ge ns[krs gS rks ikrs gS fd ;g varj vDlj rc gksrk gS tc pØokrh; fo{kksHk leqnz rV ds fudV gksrk gS vFkok mRrjh fgUn egklkxj ds }hiksa ds LFkku esa blh izdkj dk varj gksrk gSA India Meteorological Department (IMD), as a Regional Specialized Meteorological Centre (RSMC) has the responsibility of monitoring and prediction of cyclonic disturbances (CDs) including depressions and tropical cyclone (TC); collection, processing and archival of all data pertaining to CDs and preparation of best track data over the north Indian Ocean (NIO). The process of post-season analysis of CDs to determine the best estimate of a CD’s position and intensity along with other characteristics during its lifetime is described as “best tracking”. The best tracking procedure has undergone several changes world-over including NIO due to change in monitoring and analysis tools & procedure. However, the geostationary satellite remains the main tool for monitoring of location and intensity of CDs. There have been a few attempts to document the role and extent of satellite estimates in determining the best track location and intensity of CDs over the NIO. Hence, a study has been undertaken to compare the location and intensity of CDs based on best track parameters prepared by RSMC, New Delhi with those estimated by satellite division of IMD based on INSAT and Kalpana satellites. The average difference in location of CDs over the NIO, BOB and AS is about 39, 40 and 37 km respectively. The difference in location is 50 km or less in about 65% of the total cases and about 6% of the cases have a difference of 100 km or more over the NIO as a whole. It is about 62% and 6% over the BOB and about 70% and 5% over the AS respectively. Difference in location gradually decreases with increase in T number. It is about 30 km when the intensity of the system is T4.0 or more (very severe cyclonic storms and above intensity) over the BOB, AS and NIO. Considering the spatial distribution of difference in location of CDs, it is higher near the coast and decreases as we move away from the coast. The intensity in the best track agrees with the satellite estimates in about 85.5% of the cases. While the satellite based intensity is underestimated (Satellite division estimated T number is less than best track T number) in 9.5% cases, it is overestimated (Satellite division estimated T number is greater than best track derived T number) in about 5% cases over the NIO. Considering the spatial distribution, the difference occurs mostly when the CD lies near the coast or the islands in the NIO like the difference in location.